Adiksi Smartphone Terhadapusia Remaja - Andi Wasis (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2024)
Adolescence or adolescence comes from the Latin adolescere which means to grow or develop to reach maturity, where children are considered adults if they are able to reproduce. Teenagers are people aged 10-19 years, where this period is a special and important period because during this period the maturation process occurs. reproductive organs. This period is a unique transition period because physical, emotional and psychological changes occur. Adolescence is also called the transition period from childhood to adulthood where children do not want to be considered children but cannot physically be called adults. According to the World Health Organization (WHO), in 2016 globally there were 35 million people experiencing depression, 60 million people with bipolar disorder, 21 million people with schizophrenia and 47.5 million people with dementia. Depression is also a cause of death due to suicide with 850,000 cases a year. The average number of cases of depression suffered between teenagers and adults, namely in the age range 15-29 years. Data from the National Survey on Drug Use and Health in the United States, the rate of major depression in teenagers rose more than 50%, namely from 8.7% to 13.2%.